2000
DOI: 10.1093/oxfordjournals.jbchem.a022755
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance-Type DNA Methyltransferase Is Highly Expressed in Post-Mitotic Neurons and Localized in the Cytoplasmic Compartment

Abstract: Maintenance-type DNA methyltransferase (Dnmt1) is usually down-regulated in non-proliferating cells. In the present study, we detected significant expression of Dnmt1 protein in adult mouse brain where the majority of the cells are in a post-mitotic state. A significant amount of Dnmt1 protein was fractionated into the post-nuclear fraction for both cerebrum and cerebellum. The Dnmt1 in this fraction was enzymatically active. An immunofluorescence study revealed that Dnmt1 protein was mainly expressed in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 28 publications
4
79
0
Order By: Relevance
“…Sections were fixed with 3.7% formaldehyde in PBS for 10 min at room temperature. After fixation, the sections were blocked with 1% BSA, 0.1% (w/v) Triton X-100 in PBS for the anti-N-terminal Dnmt1 antibodies, or with 1% BSA, 0.4 % (w/ v) SDS, 2% (w/v) Triton X-100 in PBS for the anti-C-terminal Dnmt1 antibodies (Inano et al, 2000). For fluorescent staining, sections were incubated overnight at 4°C with the anti-N-terminal or the C-terminal Dnmt1 antibodies, and diluted 1/1,000 with corresponding blocking buffers.…”
Section: Immunocytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Sections were fixed with 3.7% formaldehyde in PBS for 10 min at room temperature. After fixation, the sections were blocked with 1% BSA, 0.1% (w/v) Triton X-100 in PBS for the anti-N-terminal Dnmt1 antibodies, or with 1% BSA, 0.4 % (w/ v) SDS, 2% (w/v) Triton X-100 in PBS for the anti-C-terminal Dnmt1 antibodies (Inano et al, 2000). For fluorescent staining, sections were incubated overnight at 4°C with the anti-N-terminal or the C-terminal Dnmt1 antibodies, and diluted 1/1,000 with corresponding blocking buffers.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…As a consequence, Dnmt1 abruptly decreases in spermatocytes at this stage (Jue et al, 1995). Recently, the transcript, of which 5' sequence is identical to that in pachytene spermatocyte, was also identified in neurons (Inano et al, 2000) and differentiated myotubes (Aguirre-Arteta et al, 2000). Interestingly, the translation product is also identified in skeletal muscle (AguirreArteta et al, 2000).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Mature neurons are enriched in Dnmts [66][67][68][69][70]. We have shown that Dnmt1 and Dnmt3a are expressed in adult mouse brain and spinal cord, and in adult human cerebral cortex and spinal cord, and that mouse and human spinal motor neurons are enriched in these proteins [70].…”
Section: Mammalian Dnmts In the Central Nervous Systemmentioning
confidence: 91%
“…Several studies have found high levels of Dnmt enzyme activity, mRNA, and protein in adult mammalian central nervous system (CNS) [66][67][68][69][70]. Mature neurons are enriched in Dnmts [66][67][68][69][70].…”
Section: Mammalian Dnmts In the Central Nervous Systemmentioning
confidence: 99%